A study of energy scavenging strategy in a tapping tree power - Abdullah Alhamzi, Belal Mohammed (2014)
Energy harvesting has become one of the newest research attraction for both academic and industry fields. The energy is captured from external sources (thermal, wind, solar, vibration and hydrodynamic) and the energy source for energy harvesters is present as ambient background and it is free. The energy can be harvested in term of sensors or direct applying which depends on the source applied to. One of the energy harvesting topologies is from tapping tree which is new topology that can be applied direct to the tree by inserting electrode into the tree while the other is into the surrounding soil. This project introduces a method for the energy to be harvested from a tree, where the voltage obtained is conducted to three types of trees (Palm, Agrawood, and Palm Oil). Both type of electrodes and pH value of the surrounding soil are considered in order to get maximum voltage. Furthermore, the depth of the electrode inserted and the height from the surrounding soil play a role for voltage variation. The maximum voltage can be obtained is from (Al Alloy with Al) electrodes, at neutral pH, dry mositure and in Palm Oil Tree which is almost 0.8V - 1.2V. However, at such small energy from tree source, converter is required to increase the power. Boost converter contains of BQ25504 IC is applied to increase the voltage from small input to 3V - 4V. As well as, buck converter with TPS62231 IC is introduced for the output voltage of the boost converter and can be applied for small voltage as 1.8V. Simulation using Tina software simulate the converters mentioned and get better results for the energy harvested with battery charging system and energy storage. Field test is conducted with the selected converter to insure the power observed from the plant. In addition, this work has been taken to enhance the growth of energy harvesting from small sources and to go further for nature sources that has a high impact for low applications in the future.